Avaliação da silvicultura a partir de sensores orbitais e suas relações com as características ambientais no município de São Gabriel/RS - Munhoz, Eliane Munhoz de (2021)
The forestry sector has advanced vigorously in the last years, with a large number of industries and products, mainly the production of wood for various uses, celulose production, papermaking and energy production. In Rio Grande do Sul, the “Southern half” region has grown the number of forest plantations, due to the installation of pulp companies in the state. In this way, professional in the environmental areas warn about the impacts that this activity can cause in the biomes of RS. Thus, the aims are to analyze the expansion of silviculture using the Landsat time series for the years “1998, 2008 and 2019” and spectral index derived from the MODIS sensor, in order to relate this information with the characteristics of compliance provisions in the zoning of silviculture in the municipality of São Gabriel. For this, the methodology comprised the acquisition of images from orbital sensors (Landsat TM and OLI) referring to 1998, 2008 and 2019 for the spatialization of data and obtaining the usage maps. In addition, data on silviculture from FEPAM and economic data from IBGE were acquired, and land use and land cover maps were compared with economic indicators associated with with environmental zoning of silviculture. In addition, the NDVI and EVI vegetation indexes of the MODIS sensor were acquired on the SATVeg platform to obtain the time series between the years 2001 to 2019. The results found for the land use and land cover maps showed that there was an increase of forestry for all years mapped with 2.27% in 1998, presented 3.03% for 2008 and 5.34% in 2019. These data indicate that in area cultivated by forestry there was a growth rate of 136% for the period studied, which shows the expansion of this rural activity. For the analysis of the conformities in the silviculture the areas calculations were made for each natural landscape unid. Thus, it was observed that the occupation limits for the years 1998 and 2008 are within the value established for each natural landscape unid. For the year 2019, the occupation area passed the maximum limit. Regarding vegetation indexes, the time profiles showed the aptitude of MODIS products to understand the development of crops. The EVI and NDVI presented characteristic behaviors of field/pasture, agriculture and from 2013 forestry plantations, each index with its specificities. In summary, the data from orbital sensors and the economic data show to be consistent in the study, therefore they consist of a set of tools that enable diagnosis and planning more closely to reality.